(3GdHdZI aj JGQjN CFeI GddZIs - (3eMeO Hf jYbhH Hf eMeO Hf EHQGgje Hf YeQ, CHh WGgQ, eLO GdOjf GdTjQGRj GdajQhRBHGOj,J (B817 (3g` s ((3bGSe Ydi GdMjOQGHGOi s)
(3ChdgG (B:s
(3GdMeO ddg MQa GdCda , GHGf GHf GSMGb GdCSOi Gdchai GdfMhi GddZhi s
(3BNQgG (B:s
(3de jJRhL hde jSJQ hde jcf dg geg EdG WdH GdYde hcGf jTQH GdWjhN Je GdcJGH s
(3fSNI CNQis
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B118s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B183 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B49 s
Keywords: (3GdJGQjNs